Risk Factors Associated with Stunting in Children Under Five in Indonesia: A Systematic Literature Review - Anita Rahmiwati; Virgina Putri Sabila; Riri Amanda Putri (Poltekita: Jurnal Ilmu Kesehatan, 2026)
Background: Stunting remains a major public health problem in Indonesia and reflects chronic nutritional deprivation during early childhood. Although national prevalence has declined in recent years, the rate remains above the World Health Organization threshold, indicating persistent and multifactorial determinants. This study aimed to identify and synthesize the main risk factors associated with stunting among children under five years of age in Indonesia. Methods: A systematic literature review was conducted using four stages: identification, screening, eligibility, and inclusion. Articles published between 2019 and 2024 were retrieved from PubMed, ScienceDirect, and Google Scholar using the keywords stunting, toddlers, and risk factors. Studies that met predefined inclusion criteria and were available in full text were analyzed. Eight articles were included in the final review. Results: The analysis identified maternal knowledge, parenting practices, low birth weight, and family economic status as significant risk factors for stunting. Low birth weight showed the strongest association, followed by maternal knowledge and parenting patterns. Conclusion: Stunting in Indonesian toddlers is predominantly influenced by modifiable maternal and early-life factors. Strengthening maternal education and prenatal care is essential to reduce stunting prevalence.